Physician Payment Reform and Hospital Referrals - Ho, Kate; Pakes, Ariel (American Economic Review, 2014)
Commercial health insurers in California use provider capitation payments to different extents. These are similar to arrangements introduced by the recent health reforms to give physicians incentives to control costs. In a previous paper we showed that patients whose insurers used capitation incentives traveled further to access lower-priced, similar-quality hospitals than other same-severity patients. This paper predicts the implied effects of a move to widespread capitation. We show that, if the introduction of capitation prompted low-capitation insurers to act like high-capitation insurers, this would generate a 4-5 percent cost saving with some reduction in patient convenience but no reduction in quality.